PENDEKATAN LINGUISTIK DALAM PENGKAJIAN SUMBER HUKUM ISLAM - NURLAILA NURLAILA (JURIS (Jurnal Ilmiah Syariah), 2016)
Approaches in Islamic studies should be appropriate with the object under studies. Linguistic approach is one of the approaches in Islamic studies whose object is scripture (manuscripts or texts). Therefore, as the main source of Islamic laws, al-Quran should use linguistics in one of its approaches. Linguistic approach which is used emphasizes upon two categories, namely linguistic and concept analyses as well. Kata kunci: pendekatan, linguistik, al-qur’an, hermeneutik.